Use of Interventions for Prevention of Serious Pregnancy Complications: Findings From a National Study in Ethiopia [15B]. (May 2017) - Getachew, Ashebir; Ricca, Jim; Rawlins, Barbara
Abstract : INTRODUCTION: Reversing Ethiopia's high maternal mortality ratio requires high access to interventions that address common causes of maternal deaths. We sought to determine levels of use of interventions and status of determinants of use that is needed by maternal health programmers. METHODS: We randomly selected 19 hospitals from a total list of hospitals in Ethiopia from which a total of 192 labors and 126 antenatal care counseling sessions were observed for use of interventions recommended by the World Health Organization regarding prevention of prolonged labor, postpartum hemorrhage, preeclampsia, & puerperal sepsis. Data on selected determinants of use were collected using key informant interviews & facility visits. Frequencies & means were computed using Excel software. Study was approved by Ethiopian Public Health Association & Johns Hopkins Bloomberg School of Public Health Ethical Review Boards. RESULTS: Only 41% of pregnant mothers were screened for preeclampsia; partograph & active management third stage of labor & infection prevention practices were used correctly in 13%, 28% & 85% of labors, respectively. Majority of providers have received in-service training on key interventions, availability of drugs was 85%. While national guideline is up to date, was not found in study health facilities. CONCLUSION: We found low use of interventions recommended for prevention of maternal complications. We recommend reviewing the quality of in-service training & availing national guidelines.